PENGARUH SISTEM INFORMASI MANAJEMEN BERBASIS KOMPUTER TERHADAP PENGAMBILAN KEPUTUSAN PERUSAHAAN - Iskandar, Jamila (Ekonomi Syariah STAI Sangatta Kutai Timur, 2019)
Management information sistem is a set of procedures / tools mutually supporting in generating information to support decision making and control in organizations. Computer-based management information sistem can be utilized to achieve the six goals of business models, improved relationship, improving decision-making, competitive advantage, and business contimuity. Business are confronted with complex problems, so the management information sistem was depeloped to support decision making in the company. Management information sistem to support decision-making in the company consists of support for the three decision-making process, there are intelligence, desingn and selection.